Lack of Protection of Pre-Immunization with Saliva of Long-Term Colonized Phlebotomus papatasi against Experimental Challenge with Leishmania major and Saliva of Wild-Caught P. papatasi - Ahmed, Sami Ben Hadj (The American Society of Tropical Medicine and Hygiene, 2010)
Immunity to saliva of Phlebotomus papatasi protects against Leishmania major infection as determined by co-inoculation of parasites with salivary gland homogenates (SGHs) of this vector. These results were obtained with long-term colonized female P. papatasi. We investigated the effect of pre-immunization with SGH of long-term colonized P. papatasi against L. major infection co-inoculated with SGH of wild-caught P. papatasi. Our results showed that pre-exposure to SGH of long-term, colonized P. papatasi do not confer protection against infection with L. major co-inoculated with SGH of wild-caught P. papatasi. These preliminary results strongly suggest that the effectiveness of a vector saliva-based vaccine derived from colonized sand fly populations may be affected by inconsistent immune response after natural exposure.